Cover Jurnal Fitopatologi Vol. 20 No. 2, Maret 2024: Cover Jurnal Fitopatologi Vol. 20 No. 2, Maret 2024 - Editors Jurnal Fitopatologi Indonesia (Jurnal Fitopatologi Indonesia, 2024)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Vol. 20 No. 2, Maret 2024.